Spontaneous transformation of a concealed to manifest posteroseptal accessory pathway requiring epicardial ablation. Issue 3 (11th April 2018) - Lee, Adam; Lindemann, James; Davison, Oscar; Wright, Daniel; Denman, Russell
Abstract: Concealed accessory pathways (APs) are considered benign as they can only sustain orthodromic atrioventricular re‐entrant tachycardia (ORT). We describe a unique case of a concealed posteroseptal AP where longitudinal surveillance following repeated failed ablation attempts due to abnormal coronary sinus (CS) anatomy revealed spontaneous development of manifest pre‐excitation. The pathway was ultimately ablated via the percutaneous epicardial approach. The potential for development of Wolff‐Parkinson‐White (WPW) syndrome in patients with concealed APs has implications for ongoing surveillance in these patients.